2015
DOI: 10.1111/are.12845
|View full text |Cite
|
Sign up to set email alerts
|

The sparing effect of phytase in plant-protein-based diets with decreasing supplementation of dietary NaH2PO4for juvenile yellow catfishPelteobagrus fulvidraco

Abstract: An 8‐week feeding trial was conducted to evaluate the sparing effect of dietary phytase on decreasing supplement of dietary sodium dihydrogen phosphate (NaH2PO4) in the diets of juvenile yellow catfish Pelteobagrus fulvidraco. Seven diets were formulated: one reference group that contained only 2% NaH2PO4; one control group that consisted of neither NaH2PO4 nor phytase; and five treatment groups supplemented with 1000 IU kg−1 phytase and 2%, 1.5%, 1%, 0.5%, 0% concentrations of NaH2PO4. Thus, dietary NaH2PO4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
8
11
0
Order By: Relevance
“…Closely similar to our results, maximum retention of protein, fat and gross energy were recorded at 900 FTU per kg addition of PHY in Catla catla fed Moringa by-products meal based diets (Shahzad et al 2016(Shahzad et al ,2018. Cheng et al (2015) recorded that plant based diets at 1000 FTU per kg addition of PHY show maximum protein and fat in Pelteobagrus fulvidraco (yellow catfish). However, Olusola and Nwanna (2014) strongly disagreed with these findings.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Closely similar to our results, maximum retention of protein, fat and gross energy were recorded at 900 FTU per kg addition of PHY in Catla catla fed Moringa by-products meal based diets (Shahzad et al 2016(Shahzad et al ,2018. Cheng et al (2015) recorded that plant based diets at 1000 FTU per kg addition of PHY show maximum protein and fat in Pelteobagrus fulvidraco (yellow catfish). However, Olusola and Nwanna (2014) strongly disagreed with these findings.…”
Section: Resultssupporting
confidence: 90%
“…Shahzad et al (2016;2020) strongly agreed with the current results of the study and observed least contents of body ash, crude fiber and moisture in Catla catla were found at 900 FTU per kg addition of PHY in Moringa leaf meal based diets. Whereas, non-significant differences were observed by Cheng et al (2015) in fish body carcass irrespective of PHY addition. Nwanna et al (2008) in contrast found that, leucaena leaf meal and Brazil nut based diets irrespective of PHY addition showed non-significant differences in lipid contents of Colossoma macropomum, Amazon tambaqui fish.…”
Section: Resultsmentioning
confidence: 70%
“…Cheng et al. () found that 50% dietary NaH 2 PO 4 could be substituted by phytase (1,000 IU/kg feed) for juvenile yellow catfish, and the improvement of digestibility of protein and P by dietary phytase resulted in the decrease in N load by 25% and P load by 31% to environment. In the present study, the supplementation of phytase in LP (12 g/kg MCP) improved the growth, the digestibility of protein, P, and reached the similar level to the PC group with 18 g/kg MCP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, imbalanced amino acid profiles and presence of antinutritional factors such as phytate usually result in poor nutrient digestibility and thus severely limit their inclusion in feed. The overall quality of plant proteins can be improved using various enzymes, such as protease (Dalsgaard et al., ; Li, Chai, Liu, Chowdhury, & Leng, ; Shi, Li, Chowdhury, Chen, & Leng, ), phytase (Cheng, Chen, Lei, Feng, & Wang, ; Morales et al., ; Vandenberg, Scott, Sarker, Dallaire, & Noüe, ) and carbohydrase (Ai et al., ; Zhou et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation